Methylation profile of genes CDKN2A (p14 and p16), DAPK1, CDH1, and ADAM23 in head and neck cancer - Calmon, Marilia F.; Colombo, Jucimara; Carvalho, Fabricio; Souza, Fatima P.; Filho, Jose F. G.; Fukuyama, Erica E.; Camargo, Anamaria A.; Caballero, Otavia L. S.; Tajara, Eloiza H.; Cordeiro, Jose A.; Rahal, Paula [UNESP] (Elsevier B.V., 2007)
Hypermethylation in the promoter region has been associated with a loss of gene function that may give a selective advantage to neoplastic cells. In this study, the methylation pattern of genes CDKN2A (alias p14, p14(ARF), p16, p16(INK4a)), DAPK1, CDH1, and ADAM23 was analyzed in 43 samples of head and neck tumors using methylation-specific polymerase chain reaction. In the oropharynx, there was a statistically significant association between hypermethylation of the DAPK1 gene and the occurrence of lymph node metastases, and in the larynx there was statistically significant evidence of an association between hypermethylation of the ADAM23 gene and advanced stages of the tumors. Thus, a correlation was observed between hypermethylation of the promoter region of genes DAPK1 and ADAM23 and the progression of head and neck cancer. (c) 2007 Elsevier B.V. All rights reserved.